Pengaruh Workplace Friendship Terhadap Organizational Citizenship Behavior Dengan Work Engagement Sebagai Variable Mediasi Pada Kantor Pusat Perumda Tirtanadi Sumatera Utara - Andre Fahreza Siregar, Muhammad (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the effect of workplace friendship on work engagement. To determine the effect of workplace friendship and work engagement on organizational citizenship behavior partially. To determine the effect of workplace friendship on organizational citizenship behavior through work engagement on employees of the Head Office of Perumda Tirtanadi, North Sumatra. The population in this study were employees of the Head Office of Perumda Tirtanadi, North Sumatra, totaling 140 people and using saturated sampling techniques. The analysis technique used was path analysis. The results of the study indicate that workplace friendship has a significant effect on organizational citizenship behavior on employees of the Head Office of Perumda Tirtanadi, North Sumatra. Workplace Friendship has a significant effect on Work Engagement on employees of the Head Office of Perumda Tirtanadi, North Sumatra Work Engagement does not mediate the effect of Workplace Friendship on Organizational Citizenship Behavior on employees of the Head Office of Perumda Tirtanadi, North Sumatra